2018
DOI: 10.1007/s40262-018-0642-9
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism-Based Population Pharmacokinetic Analysis Assessing the Feasibility of Efavirenz Dose Reduction to 400 mg in Pregnant Women

Abstract: BackgroundReducing the dose of efavirenz can improve safety, reduce costs, and increase access for patients with HIV infection. According to the World Health Organization, a similar dosing strategy for all patient populations is desirable for universal roll-out; however, it remains unknown whether the 400 mg daily dose is adequate during pregnancy.MethodsWe developed a mechanistic population pharmacokinetic model using pooled data from women included in seven studies (1968 samples, 774 collected during pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…However, efavirenz is still widely used as the preferred first‐line antiretroviral agent in the middle‐ and low‐ income countries, including Malaysia 18 . Efavirenz dose of 400 mg daily was reported to reduce efavirenz toxicities, 12 and was noninferior to the usual 600‐mg daily dose in adult HIV‐positive patients 19–22 . Nevertheless, none of the previous studies evaluated the drug response of efavirenz dose reduction among HIV‐positive smokers.…”
Section: Introductionmentioning
confidence: 99%
“…However, efavirenz is still widely used as the preferred first‐line antiretroviral agent in the middle‐ and low‐ income countries, including Malaysia 18 . Efavirenz dose of 400 mg daily was reported to reduce efavirenz toxicities, 12 and was noninferior to the usual 600‐mg daily dose in adult HIV‐positive patients 19–22 . Nevertheless, none of the previous studies evaluated the drug response of efavirenz dose reduction among HIV‐positive smokers.…”
Section: Introductionmentioning
confidence: 99%
“…Kreitchmann reported that C24 (24 h post-dose) concentrations during the second and third trimester were similar to the C24 concentrations seen in the ENCORE1 study with a 400 mg dose [23,27]. However, the increased variability due to CYP2B6's polymorphism could lead to the subtherapeutic, systemic exposure in extensive metabolisers, as predicted by PBPK studies [29,30].…”
Section: Efavirenzmentioning
confidence: 68%
“…31 Emerging data using the lower dose in pregnancy also suggest that adequate exposure is maintained along with reduced toxicities expected. 32,33 Research regarding the use of EFV 400 mg in patients with concomitant tuberculosis is still warranted.…”
Section: Background/efficacymentioning
confidence: 99%